Modelagem e simulação da operação de sistemas de geração com fontes renováveis de energia suprindo minirrede de distribuição - FERREIRA, Andreza Cardoso (Universidade Federal do Pará, 2018)
This work is about the development of computational models in Simulink/Matlab workspace, that simulate the operation in islanded or grid connected mode of electrical energy distribution microgrid with hybrid resources, belonging to the Group of Studies and Development of Energy Alternatives (Grupo de Estudos e Desenvolvimento de Alternativas Energéticas - GEDAE) of Universidade Federal do Pará (UFPA), in the Campus of Belém. This paper also describes the hybrid systems and its components (generation systems, power conditioners, microgrid and proposed loads), also the mathematical models, presenting the equations of components applied to dynamic studies. Then the component models that compose the system are validated and analyzed based on the experimental data. It also presents the integration of the proposed models of the hybrid system, simulating three different strategies or modes of operation as a case study. The developed model has the function of helping these studies, simplifying the analysis and providing different possibilities of simulations in short processing time. The principal aim of the work is to make available a computational model able to simulate in detail the behavior of a hybrid system in connected or isolated of conventional power grid operation conditions.